Design of bismuth oxide nanoparticles as lightweight aggregate in cement composites against X‐rays. Issue 2 (6th February 2019) - Restuccia, Luciana; Favero, Alberto; Jagdale, Pravin; Cavalot, Gabriella; Ferro, Giuseppe Andrea
Abstract: Nowadays, heavy concrete is becoming one of the most commonly used materials against X‐ray radiation (medical or nuclear). This type of concrete is enriched by heavy aggregates with high density and/or high atomic number such as magnetite or barite, which allow to obtain an appreciable shielding effect but may present problems related to high manufacturing costs. Moreover, very heavy concretes can be achieved with iron or lead shot as aggregate, but in this case, the big problem is related to the toxicity and harmful for human health. In this research work, bismuth—a cheap, nontoxic, and biocompatible element, characterized by having a high atomic number Z (Z = 83)—has been used as additive in cement mixture, with the purpose to indagate its effectiveness as shielding agent and to analyze the mechanical strength response.